Types of strategies in dialogical translation model of document discourse - Kavaleuskaya, Iryna I. (Journal of the Belarusian State University. Philology, 2018)
The paper discusses the types of strategies of document translation from the perspective of the dialogical theory focusing on the interactive nature of intercultural business communication. It distinguishes the strategies of desubjectivization of the source text content, face saving and adaptation of space and time implications to the target culture. The strategies are associated with the categories of epistemity, actoriality, spatiality and temporality as the common intersubjective space coordinates of translation discourse. The dialogical translation analysis of documents reveals their translation tactics and techniques. The intercultural communication participants’ relations are considered as the main criterion for their classification. The study of these relations is assumed to allow for more detailed classification of dialogical translation strategies of documents as well as other genres.
Keywords: dialogical translation model; document discourse; intersubjective space; intercultural business communication; strategy of translation; tactic of translation; technique of translation